PJMHS 2022
DOI: 10.53350/pjmhs20221611366
|View full text |Cite
|
Sign up to set email alerts
|

Information Dissemination during COVID-19 Pandemic among Postgraduate Allied Health Sciences Students in Pakistan

Abstract: Purpose: This study determines the information dissemination during the Covid-19 pandemic and examine the impact on the educational activity of postgraduate students in Allied Health Sciences institute in Pakistan. Methodology: Present quantitative study is based on survey method that was carried out to assess the effectiveness of information dissemination during Covid-19 pandemic among postgraduate allied health science students in different universities in Lahore Pakistan. Finding: The response rate of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…They concluded that when anger is suppressed, it leads to the underlying cause of anxiety and depression. Therefore, medical students who will have to deal with every kind of patient are needed to know and practice 16,17,18,19,20,21 how to manage anger. And the best way to manage and control anger is the one that Islam teaches us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that when anger is suppressed, it leads to the underlying cause of anxiety and depression. Therefore, medical students who will have to deal with every kind of patient are needed to know and practice 16,17,18,19,20,21 how to manage anger. And the best way to manage and control anger is the one that Islam teaches us.…”
Section: Discussionmentioning
confidence: 99%
“…They will improve their education and collection of resources. 16,17,18,19,20,21 Therefore, by conducting this research we were aiming to focus on medical college students as their lifestyle is comparatively more stressful than ordinary college goers 6 . The aim of this study is to asses knowledge, attitude and practice of anger management among medical students and its effect on their daily life and position in the society.…”
Section: Introductionmentioning
confidence: 99%
“…The heath literacy is mandatory for any disease and facilitates the patients with resources, databases, and trainings about disease. [26][27][28][29][30][31][32]…”
Section: Discussionmentioning
confidence: 99%
“…Research plays an important role in dissemination of correct information amongst the general population about prevalent diseases, their complications, new breakthroughs in treatment, dismission of myths; for example, the role of research papers and resources available in e-libraries in spreading the right information was quite effective during the covid pandemic 9,10,11 . In addition to that certain case studies and cross-sectional studies carried out by university students help in raising awareness about important medicine related social issues, for example a study done by a medical student and postgraduates showed a negative link among caregiver burden and quality of life of caregivers of patients with chronic illnesses (schizophrenia in this case) 12 .…”
Section: Introductionmentioning
confidence: 99%